A Prospective Clinical Study on Postoperative Complications of Prostate Biopsy Following COVID-19 Infection at a Tertiary Hospital in Taizhou, China - Dong-sheng Zhang; Yu-yi Chen; Jia-jia Zhu; Rong Wang; Liang-xue Sun (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusion: The incidence of postoperative complications of prostate biopsy in post-COVID-19 patients, who currently have no symptoms of COVID-19 infection, was comparable to patients with no history of COVID-19 infection. In clinical practice, for males with a history of controlled COVID-19 infection, the risk of postoperative complications from prostate biopsy should not be a major concern.